Effect of Cooling Rate on the Longitudinal Modulus of Cu3Sn Phase of Ag-Sn-Cu Amalgam Alloy (Part II) - R. H. Rusli (Faculty of Dentistry, Universitas Indonesia, 2015)
Effects of cooling rate (at the time of solidification on the elastic constants of Cu3Sn phase of Ag-Sn-Cu dental amalgam alloy were studied. In this study, three types of alloys were made, with the composition Cu-38-37 wt% Sn by means of casting, where each alloy was subjected to different cooling rate, such as cooling on the air (AC), air blown (AB), and quenched in the water (WQ). X-ray diffraction, metallography, and Scanning Electron Microscopy with Energy Dispersive Spectroscopy studies of three alloys indicated the existence of Cu3Sn phase. Determination of the modulus of elasticity of Cu3Sn (ε) phase was carried out by the measurement of longitudinal and transversal waves velocity using ultrasonic technique. The result shows that Cu3Sn (ε) phase on AC gives higher modulus of elasticity values than those of Cu3Sn (ε) on AB and WQ. The high modulus of elasticity value will produce a strong Ag-Sn-Cu dental amalagam alloy.